Frecuencia de aparicion de dos especies de neuropteros en la provincia de La Habana - Rijo, E.=700 1 Acosta, N.; Calvo, D.
(Es, En)
Ilus., 7 ref.
Keywords: CITRUS PARADISI; CHRYSOPA; NEUROPTERA; ESPECIES NUEVAS; CUBA; TORONJA; CHRYSOPA HABANA; NODITA DIMIDIA